Panduan belajar wordperfect 6.0 for windows cara cepat dan mudah belajar wordferfect - REBER, Susan R (Elex Media Komputindo, 1993)
Panduan belajar wordperfect 6.0 for windows cara cepat dan mudah belajar ....